Penerapan Metode Instalasi Tangki Cryogenic Di Rumah Sakit Untuk Mewujudkan Konsep Green Economic Dalam Bentuk Green Logistic (Studi Kasus di PT. Sentosa Ultra Gasindo) - Sabaruddin, La Ode (Majalah Ilmiah Bijak, 2020)
The embodiment of green economy is increasingly sought by various companies throughout the world. This is done as a form of responsibility and care to help preserve nature and maintain the survival of living things in it.PT. Sentosa Ultra Grasindo as one of the companies engaged in the gas industry that provides various types of gas, one of which is medical gas applying the cryogenic tank installation method to help realize the green economy. This study aims to determine how the impact of the application of Cryogenic Tank installation methods in hospitals to the realization of green economy in the form of green logistics for oxygen distribution activities to XYZ Hospital, which is its client.This is a qualitative descriptive study using primary data types obtained from in-depth interviews and observations of related parties. The results showed that the method of installing cryogenic tanks in hospitals was considered to be more environmentally friendly and realize effectiveness and efficiency for PT. Sentosa Ultra Gasindo and for XYZ Hospital.